FRI0388 Monitoring Local Therapy in Sjögren's Syndrome with Virtual Touch Tissue Quantification Sonography. (9th June 2015) - Hofauer, B.; Bas, M.; Heiser, C.; Schukraft, J.; Mansour, N.; Knopf, A.
Abstract : Background: Evaluation of various sonographic techniques in diagnosis and follow-up of salivary gland involvement in Sjögren's Syndrome is part of on-going investigations. Virtual Touch Tissue Quantification (VTTQ) sonography, as modern sonographic method, enables the objective measurement of parotid and submandibular gland stiffness in SS, as recent reports could demonstrate. Consequently the consideration emerges, if VTTQ is suitable to monitor the response to local or systemic treatment. Objectives: Is Virtual Touch Tissue Quantification sonography suitable to monitor the response to a liposomal local therapy in Sjögren's Syndrome? Methods: 50 patients with pSS, diagnosed according to the AECG criteria, were included (group 1). As comparison group 50 patients were chosen with condition following radiotherapy of the head and neck region (including the salivary glands, group 2). Clinical data were collected and sonographic examination including VTTQ was performed. Subjective symptoms were evaluated via visual analogue scales (VAS). After a two-months period of liposomal local therapy sonographic examination including VTTQ was repeated and subjective symptoms were re-evaluated. In group 1, right side parotid and submandibular glands were examined; in group 2, the – in regard to the irradiated side – ipsi- and contralateral parotid and submandibular glands were examined. Results: Before local treatment, the mean VTTQ value of parotid glands in group 1 was 2.99m/s 2 (SD 0.93); in group 2, the mean VTTQ value of the ipsilateral parotid glands was 2.35m/s 2 (SD 0.7) and of the contralateral parotid glands was 2.14m/s 2 (SD 0.55). Mean VTTQ value of the submandibular glands in group 1 was 2.15m/s 2 (SD 0.57); in group 2, the mean VTTQ value of the ipsilateral submandibular glands was 2.27m/s 2 (SD 0.69) and of the contralateral submandibular glands was 2.17m/s 2 (SD 0.57). After two-months treatment with locally applied liposomes a significant decline of VTTQ values could be observed both in parotid glands in group 1 (2.33m/s 2, SD 0.70, p<0.001) and in ipsilateral (2.20m/s 2, SD 0.56, p=0.01) and contralateral (2.07m/s 2, SD 0.50, p=0.047) parotid glands in group 2. Submandibular glands did not show any significant change in both groups. A significant reduction of the subjective sensation of xerostomia could be observed (p=0.0001). Conclusions: With the application of Virtual Touch Tissue Quantification sonography a decline in parotid gland stiffness could be observed both in Sjögren's Syndrome and condition following radio therapy accompanied by a significant improvement of the subjective sensation of xerostomia. The seromucous submandibular glands did not show any changes compared to the serous parotid glands. Disclosure of Interest: None declared